Sistem Keamanan Pintar Menggunakan Kamera Berbasis OpenCV - Abdullah Sani; Randa Julianto; Hana Mutialif Maulidiah; Muhammad Jaka Wimbang Wicaksono (Politeknik Negeri Batam, 2023)
Security is a condition that is free from denger, every individual has the right to feel safe in daily life or activities. As time goes by, the security level can be disrupted or dangerous things can happen beyond prediction, in other words, it can happen suddenly, therefore of course there must be a system development as a medium for anticipating this. With the aim of develop the system, it is necessary to design a system that can reduce crimes that are beyond human expectations. This system is called the Smart Security System which is a development of CCTV in general, this system uses cameras and smartphones as information media that will provide notifications to each individual to get notifications regarding real-time conditions in areas under camera surveillance via telegram. This system is assisted by Machine Learning in the form of OpenCV which is programmed on a Raspberry pi4 device which is connected directly to the camera to detect people ormovement in areas under CCTV monitoring so that it can immediately provide information to users which is sent via telegram in the form of video. It is hoped that with this system the level of security can be more effective so as to reduce the risk of theft in a room. From the results of the tests that have been carried out, it is found that to determine the effectiveness of the work of this study, an optimal distance is needed with a minimum distance range of 2 meters - 10 meters from the front of the camera and bright lighting